Covariant constructive gravity - Reinhart, Tobias; Alex, Nils (15th Marcel Grossmann Meeting on Recent Developments in Theoretical and Experimental General Relativity, Astrophysics, and Relativistic Field Theories, MG 2018, 2022)
We present a method of constructing perturbative equations of motion for the geometric background of any given tensorial field theory. Requiring invariance of the gravitational dynamics under spacetime diffeomorphisms leads to a PDE system for the gravitational Lagrangian that can be solved by means of a power series ansatz. Furthermore, in each order we pose conditions on the causality of the gravitational equations, that en- sure coevolution of the matter fields and the gravitational background is possible, i.e. gravitational equations and matter equations share the same initial data hypersurfaces.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Causality; Constructive gravity; Diffeomorphism invariance